Organizational commitment in the private and public sectors: a regression analysis based on personality traits, subjective wellbeing, organizational orientations, and perceived employment uncertainty in Serbia - Todorović, Dušan; Mitić, Petar M.; Stojiljković, Nenad; Olanescu, Mihai; Suciu, Adrian; Popa, Danut (Frontiers in Psychology, 2024)
This study aims to explain the variability in organizational commitment by examining a range of individual and organizational factors. The predictors include personality traits from the HEXACO model, organizational orientations, subjective wellbeing, perceived employment uncertainty, duration of employment, and income satisfaction. The sample consisted of 1,127 employees, with 49.4% from the private sector and 50.6% from the public/state-owned sector. Multiple regression analysis revealed that the models were statistically significant for both sectors. Public sector employees demonstrated higher levels of continuance commitment, likely due to job security, while private sector employees exhibited higher levels of affective and normative commitment. The model accounted for 51.8% of the variance in organizational commitment for public sector employees and 39.2% for private sector employees. These findings underscore the distinct commitment patterns between sectors and emphasize the role of both dispositional and contextual factors in shaping organizational commitment.